DESAIN GEOMETRI SCREW PRESS DENGAN METODE NUMERIK ELEMEN HINGGA - Bagus Budiwantoro; Arief Teguh Hermawan (Mesin, 2002)
Screw Press is one of the main component of Crude Palm Oil (CPO) extraction machine. Until these days, the Indonesian CPO industries still import this component from Malaysia with longer delivery-order period that means a problem for productivity. This paper was written as alternative solution for Screw Press geometrical design by doing some engineering analysis. The analysis was limited to the geometrical design matter of component by modifying the fillet part and thickness of screw, and also analyzing the surface pressure of component. Finite element model was developed using MSC.Nastran software package. The results of overall analysis show that the reduction rate of stress concentration as the effect of increasing fillet radius is 12% per 5 mm and the reduction rate of maximum stress as effect of increasing screw thickness is 9% per 2 mm. Surface pressure caused by loading is linear with fillet radius and its value is about 0,1 times of the mean principal stresses.